2014
DOI: 10.1080/09205063.2014.950505
|View full text |Cite
|
Sign up to set email alerts
|

Axially aligned 3D nanofibrous grafts of PLA–PCL for small diameter cardiovascular applications

Abstract: Axially aligned nanofibrous matrices were evaluated as small diameter cardiovascular grafts. Grafts were prepared using the poly(L-lactic acid) (PLA) and poly(ε-caprolactone) (PCL) physical blends in the ratios of 75:25 and 25:75 with the dimension of (40 × 0.2 × 4) millimeter by electrospinning using dynamic collector (1500 RPM). Hydrophobicity and tensile stress were significantly higher in PLA-PCL (75:25), whereas tensile strain and fiber density were significantly higher in PLA-PCL (25:75). Properties such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…Many studies have focused on the utility of electrospinning for applications in small three‐dimensional fiber‐based tissue replacement scaffolds/grafts . It has had the greatest success in tissue repair/replacement applications like skin, cartilage, nerves and blood vessels .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have focused on the utility of electrospinning for applications in small three‐dimensional fiber‐based tissue replacement scaffolds/grafts . It has had the greatest success in tissue repair/replacement applications like skin, cartilage, nerves and blood vessels .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on the utility of electrospinning for applications in small three-dimensional fiber-based tissue replacement scaffolds/grafts. 5,[35][36][37][38][39] It has had the greatest success in tissue repair/replacement applications like skin, 40,41 cartilage, 16 nerves 39 and blood vessels. 3 However, the application of electrospun grafts in thicker tissues, like muscle and even full-thickness skin defects, has had notably less success.…”
Section: Figurementioning
confidence: 99%
“…Poly (l-lactic acid-co-ε-caprolactone) (PLCL) is a nontoxic, biodegradable and synthetic co-polymer of poly (L-lactic acid) (PLLA) and poly (ε-caprolactone) (PCL; Jin et al, 2009). PLCL has been investigated as a biomaterial for tissue engineering, such as wound healing, formation of cartilage and cardiovascular applications (Jin et al, 2011; He et al, 2013; Sankaran et al, 2014). Moreover, collagen/PLCL nanofibrous scaffolds and silk fibroin/PLCL nanofibrous scaffolds have been proposed to be considered as potential candidates for nerve tissue engineering (Prabhakaran et al, 2009; Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some expanded ePTFE grafts have shown only a 10 6 7% attachment rate of endothelial cells; a high proportion of cells was washed off from the lumen when the graft was exposed to pulsatile blood flow. Although degradable synthetic materials are popular such as PGA, PLA (21), and PLGA (22), in fact, most of these materials are not, per se, suitable for endotheliocyte adhesion. Data from a study showed that fewer than 30% of cells remained on the surface after only 1 h of exposure to physiological levels of shear stress.…”
Section: Discussionmentioning
confidence: 99%